1997
DOI: 10.1097/00007632-199703150-00025
|View full text |Cite
|
Sign up to set email alerts
|

Intertransverse Approach for Extraforaminal Herniations

Abstract: The patho-anatomical characteristic of the entity is compression of the spinal nerve outside the foramen. Intertransverse discectomy is a rational technique-its advantages are that the spinal canal is not opened, spine stability is maintained, and multiple disc herniation can be managed through a single posterior midline incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Far lateral or extreme lateral disc herniation primarily indicates that disc herniation is beyond the lateral intervertebral space. [15][16][17] Foraminal disc herniations occur beneath the facet, and extraforaminal herniations occur outside of the facet. An anatomic and roentgenographic study showed that the DRGs are directly inferior to the pedicle in 90% of the cases in human.…”
Section: Discussionmentioning
confidence: 99%
“…Far lateral or extreme lateral disc herniation primarily indicates that disc herniation is beyond the lateral intervertebral space. [15][16][17] Foraminal disc herniations occur beneath the facet, and extraforaminal herniations occur outside of the facet. An anatomic and roentgenographic study showed that the DRGs are directly inferior to the pedicle in 90% of the cases in human.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar disc herniations usually occur in the spinal canal, compressing the nerve roots, cauda equina, and/or DRG, causing lower extremity radicular pain. Far lateral or extreme lateral disc herniation primarily indicates that disc herniation is beyond the lateral intervertebral space ( Epstein et al, 1990; Wang et al, 1997; Gioia et al, 1999 ) . According to previous anatomical studies, the center of the lumbar DRG is adjacent to the lateral intervertebral disc in 32% of the patients studied ( Cohen et al, 1990 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, intertransverse ligament is not so much functionally important anatomical structure but there are many vessels beneath the ligament. The blood supply to the root has been shown to be critically dependent on the lateral radicular vessels (24,25) . Therefore, ischemic changes due to the disc fragment compression may be the cause of the acuteness of the symptoms seen in FLLDHs.…”
Section: Study Limitationsmentioning
confidence: 99%